Factors of Purchasing Decisions of Consumers of Blukid Residence 3 Housing in Sidoarjo - Regina Ayu Kusuma Wardani (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study aims to find out and analyze what factors consumers consider in making the decision to buy a house in Blukid Residence 3 Housing. The object studied in the study was Blukid Residence 3 Housing located in the city of Sidoarjo, East Java. In 2019 marketing experienced a decline in interest in site visits, resulting in a decline in sales in our housing. The method used in this study is a quantitative method. Researchers used Confirmatory Factor Analysis (CFA) to analyze the data. This research was conducted at Blukid Residence 3 Housing located in Sidoarjo with a sample of 97 respondents.